Dark Production of Extracellular Superoxide by the Coral Porites astreoides and Representative Symbionts - Zhang, Tong; Diaz, Julia M.; Brighi, Caterina; Parsons, Rachel J.; McNally, Sean; Apprill, Amy; Hansel, Colleen M. (Frontiers in Marine Science, 2016)
The reactive oxygen species (ROS) superoxide has been implicated in both beneficial and detrimental processes in coral biology, ranging from pathogenic disease resistance to coral bleaching. Despite the critical role of ROS in coral health, there is a distinct lack of ROS measurements and thus an incomplete understanding of underpinning ROS sources and production mechanisms within coral systems. Here, we quantified in situ extracellular superoxide concentrations at the surfaces of aquaria-hosted Porites astreoides during a diel cycle. High concentrations of superoxide ( 10's of nM) were present at coral surfaces, and these levels did not change significantly as a function of time of day. These results indicate that the coral holobiont produces extracellular superoxide in the dark, independent of photosynthesis. As a short-lived anion at physiological pH, superoxide has a limited ability to cross intact biological membranes. Further, removing surface mucus layers from the P. astreoides colonies did not impact external superoxide concentrations. We therefore attribute external superoxide derived from the coral holobiont under these conditions to the activity of the coral host epithelium, rather than mucus-derived epibionts or internal sources such as endosymbionts (e.g., Symbiodinium). However, endosymbionts likely contribute to internal ROS levels via extracellular superoxide production. Indeed, common coral symbionts, including multiple strains of Symbiodinium (clades A to D) and the bacterium Endozoicomonas montiporae LMG 24815, produced extracellular superoxide in the dark and at low light levels. Further, representative P. astreoides symbionts, Symbiodinium CCMP2456 (clade A) and E. montiporae, produced similar concentrations of superoxide alone and in combination with each other, in the dark and low light, and regardless of time of day. Overall, these results indicate that healthy, non-stressed P. astreoides and representative symbionts produce superoxide externally, which is decoupled from photosynthetic activity and circadian control. Corals may therefore produce extracellular superoxide constitutively, highlighting an unclear yet potentially beneficial role for superoxide in coral physiology and health.